ABILITY TEST OF SEVERAL ANTAGONISTS TO CONTROL POTATO BACTERIAL WILT IN THE FIELD - Soesanto, Loekas; Manan, Abdul; Wachjadi, Muljo; Mugiastuti, Endang (AGRIVITA, Journal of Agricultural Science, 2013)
The research objective was to know ability of antagonistic microbes to control bacterial wilt on potato in the field. This research was carried out at Serang Village, Karangreja Subdistrict, Purbalingga Regency from June up to August 2012. The antagonist, originally isolated from potato field, was Bacillus sp. B2 and B4, and Pseudomonas sp. P19 and P20. Based on the research result, Pseudomonas P19 could control the disease on potato with delaying incubation period of 78.95%, suppressing disease intensity of 51.57%, decreasing final pathogenic population of 99.74%, and inducing plant resistance with increasing saponin, tannin, and glycoside content. However, the antagonist could not increase growth and yield of potato. Â Keywords: antagonistic microbes, bacterial wilt, potato